A autonomia dos usuários de um Centro de Atenção Psicossocial nas relações cotidianas - Clasen, Bianca Neme (2010)
The autonomy concerns the condition of self-determination and self-governance. Considering this affirmation, this study it had as objectives to know manifestations of the autonomies attitudinal, functional and emotional in expression of daily relations of users of a CAPS of municipality of Alegrete-RS. This is a qualitative, descriptive and analytical study. The subjects were 11 users. The data was collected through interviews held in the second semester of 2006. The data were analyzed in the light of the theoretical referential that understands the autonomies attitudinal, functional and emotional. With regard to the attitudinal autonomy it is observed it has on the part of the users the manifestation of the essential aptitudes and desires in the attitudes in areas of self care, in establishing interpersonal relations and for the work. The autonomy for the self care appears, over all, in the expression of practices related to hygiene, health care of the body through physical exercise and the commitment of some users to not leave to have the continuous supply of psychotropic drugs by the System of Health to all those who use them. The attitudinal autonomy to establish interpersonal relationships might be perceived through the exercise of desire and the decision of "with who", "in which situations" and "how to relate to, manage or intervene situations . The attitudinal autonomy for work emerges in the protected context of the work, in workshops, when the work happens in the space of the CAPS. Concerning the functional autonomy, it is observed that majority of subjects reveals to be capable of making decisions by themselves and trace strategies to achieve and to complete the goals. At this research, the functionality is characterized by maintain regularity, allowing the cases of decision making recur in daily life, while the attitudinal is an individual expression or even sporadic. The selfcare is portrayed through systematic practices of health care of the body, the maintenance of psychiatric treatment and the possibility to keep the functionality of daily conduits through the benefit that many users receive from the government. The autonomy to take care of domestic tasks was also evident in the speeches. Relations of daily care with the other, as well as the condition of being able to circulate for the territory seeking to establish or maintain relations of friendship and exchange had been also observed as important conditions for the exercise of functional autonomy. The autonomy to practice the work appears under different levels of independence as a condition in which subjects are, oscillating since the situation of accomplishment of assisted work, in protecting environment and with therapeutic intent, until to the 9 exercise of formal and wage-earning employment. The emotional autonomy is also an attribute in the reports, denoting the condition of self-reliance and emotional independence in relation to other people. This condition appears under the form of self-worth and the establishment of supportive relations, fueled by self-confidence and self-efficacy. Closes up, so that the purpose of the research are included in all testimonials, so the above autonomy were present in daily relationships of eleven subjects.